A vitamin E long-chain metabolite and the inspired drug candidate α-amplexichromanol relieve asthma features in an experimental model of allergen sensitization. (July 2022) - Cerqua, Ida; Neukirch, Konstantin; Terlizzi, Michela; Granato, Elisabetta; Caiazzo, Elisabetta; Cicala, Carla; Ialenti, Armando; Capasso, Raffaele; Werz, Oliver; Sorrentino, Rosalinda; Seraphin, Denis; Helesbeux, Jean-Jacques; et al.
Abstract: Benefits for vitamin E intake in diseases with inflammatory components have been described and related in part, to endogenously formed metabolites (long-chain metabolites, LCM). Here, we have evaluated the role of LCM in relieving asthma features. To this aim, the endogenous vitamin E metabolite α-13′-carboxychromanol (α-T-13′-COOH) that acts as potent 5-lipoxygenase inhibitor has been administered either intraperitoneally or by oral gavage to BALB/c mice sensitized by subcutaneous injection of ovalbumin (OVA). We also have taken advantage of the metabolically stable α-T-13′-COOH derivative α-amplexichromanol (α-AC). Intraperitoneal treatment with α-T-13'-COOH reduced OVA-induced airway hyperreactivity (AHR) as well as peri-bronchial inflammatory cell infiltration. α-AC was more efficacious than α-T-13'-COOH, as demonstrated by better control of AHR and in reducing subepithelial. Both compounds exerted their protective function by reducing pulmonary leukotriene C4 levels. Beneficial effects of α-AC were coupled to inhibition of the sensitization process, as indicated by a reduction of IgE plasma levels, lung mast cell infiltration and Th2 immune response. Metabololipidomics analysis revealed that α-AC raises the pulmonary levels of prostanoids, their degradation products, and 12/15-lipoxygenase metabolites. Following oral administration, the pharmacodynamically different profile in α-T-13′-COOH and α-AC was abrogated as demonstrated by a similar and improved efficacy in controlling asthma features as well as by metabololipidomics analysis. In conclusion, this study highlights a role for LCM and of vitamin E derivatives as pharmacologically active compounds that ameliorate asthmatic features and defines an important role for endogenous vitamin E metabolites in regulating immune response underlying the sensitization process. Graphical Abstract: ga1 Highlights: Vitamin E long-chain metabolites relieve allergen-induced bronchial hyperreactivity. Vitamin E long-chain metabolites inhibit Th2 immune response induced by allergen. Vitamin E long-chain metabolites modulate anti- and pro-inflammatory lipid mediators